PSA Discovery of the New Pandemic A Contract Cheating - Hadijah, Ahmad (2023)
Students are required to create Public Service Announcements (PSAs) in Kursus Integriti dan Anti-Rasuah (KIAR) - UHE3432 as one of the assessments. They are tasked with creating a video that will convey the message of the KIAR content, either the penalties, true bribery cases, whistle-blower protection, or the importance of integrity. The student should also be able to explain the message of the PSA and how the contents of KIAR are reflected in the PSA. The PSA should be distributed to the general public to raise public awareness of KIAR and its contents.